Total fitness : an advanced training guide for the sportsperson - Martin, Nita A. (Ramsbury, Marlborough : The Crowood Press, 2010)
Introduces the various components of fitness, and examines the benefits of training. This book describes and illustrates exercises for developing the following: strength, strength endurance, power, plyometrics, stamina, speed, agility, coordination, posture, flexibility and balance
1. Introduction -- 2. Training tips -- 3. Understanding your body -- 4. Strength, strength endurance and power -- 5. Plyometrics -- 6. Stamina -- 7. Speed -- 8. Agility -- 9. Co-ordination -- 10. Posture -- 11. Flexibility -- 12. Balance -- 13. Quick reference guides
Includes bibliographical references and index
Keywords: Athletes -- Training of; Physical education and training